2021
DOI: 10.1083/jcb.202005080
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling establishes the microtubule polarity in neurons through regulation of Kinesin-13

Abstract: Neuronal polarization is facilitated by the formation of axons with parallel arrays of plus-end-out and dendrites with the nonuniform orientation of microtubules. In C. elegans, the posterior lateral microtubule (PLM) neuron is bipolar with its two processes growing along the anterior–posterior axis under the guidance of Wnt signaling. Here we found that loss of the Kinesin-13 family microtubule-depolymerizing enzyme KLP-7 led to the ectopic extension of axon-like processes from the PLM cell body. Live imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 88 publications
3
17
0
Order By: Relevance
“…We determined the polarity of the microtubules from the direction of microtubule growth from the plus ends, as seen in the kymographs (Figure 3B) from the regions of interest in the anterior and posterior processes of PLM neuron (Figure 3A). In the wild-type background, the PLM anterior process had the majority of the EBP-2::GFP movements away from the cell body (plus-end-out, green trace), while in the posterior process, EBP-2::GFP movements were seen both away from and towards the cell body (minus-end-out, magenta trace, Figure 3A-B), as reported before (7). We plotted the fraction of microtubule tracks with ‘plus-end-out’ or ‘minus-end-out’ orientation (Figure 3C).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…We determined the polarity of the microtubules from the direction of microtubule growth from the plus ends, as seen in the kymographs (Figure 3B) from the regions of interest in the anterior and posterior processes of PLM neuron (Figure 3A). In the wild-type background, the PLM anterior process had the majority of the EBP-2::GFP movements away from the cell body (plus-end-out, green trace), while in the posterior process, EBP-2::GFP movements were seen both away from and towards the cell body (minus-end-out, magenta trace, Figure 3A-B), as reported before (7). We plotted the fraction of microtubule tracks with ‘plus-end-out’ or ‘minus-end-out’ orientation (Figure 3C).…”
Section: Resultssupporting
confidence: 81%
“…Additionally, PLM also has a short posterior process (double-sided white arrow, Figure 1A). Recently, we showed that loss of kinesin-13/KLP-7 microtubule depolymerizing protein, leads to multiple axon-like phenotype in ALM neuron (orange arrow, Figure 1A), and the overgrowth phenotype of the PLM posterior process (double-sided white arrow, Figure1A),Figure 1A) due to excessive stabilization of the microtubule cytoskeleton (7). Destabilization of microtubules using colchicine or loss of tubulin subunits suppresses the axon overgrowth phenotype seen in the klp-7 mutant (7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed the development of two mechanosensory neurons, anterior lateral mechanosensory (ALM) and posterior lateral mechanosensory (PLM) neurons ( Figure 1C ) because the tiling between PLM and ALM neurons are strictly regulated by microtubule regulating factors, such as kinesin-13. Previous studies have shown worm mutants with more stable microtubules have defects in tiling between PLM and ALM ( Puri et al, 2021 ). In wild-type animals, the axonal tip of PLM neurons does not reach the cell body of ALM without overlapping with each other (wild-type in Figure 1D and E ; Gallegos and Bargmann, 2004 ).…”
Section: Resultsmentioning
confidence: 99%
“… Weiner et al (2020) showed that in Drosophila , some Wnt signaling proteins, such as Fz, LRP5/6 or Axin, recruit the MT core-nucleation protein γ-Tubulin to endosomes in the dendritic branch points, enabling local MT nucleation and indicating that extracellular Wnt signaling can regulate local MT nucleation in dendrites. In addition, two other recent studies have revealed that the Wnt pathway controls axon specification in developing neurons by organizing the polarity of MT networks both in the axon ( Stanganello et al, 2019 ) and in non-axonal neurites ( Puri et al, 2021 ). Plus, it is known that local MT nucleation contribute the MT arrangements in these compartments ( Sánchez-Huertas et al, 2016 ; Cunha-Ferreira et al, 2018 ).…”
Section: Microtubule-associated Proteins In Axon Guidancementioning
confidence: 99%